2005
DOI: 10.1007/s10029-004-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free repair versus modified Bassini technique (Andrews technique) for strangulated inguinal hernia: a comparative study

Abstract: The presence of a strangulated inguinal hernia cannot be considered a contraindication for the use of a prosthetic mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 15 publications
4
49
0
16
Order By: Relevance
“…Bessa et al [30] stated that there was no difference between elective or emergency mesh use in terms of postoperative complications and that mesh could be used safely. Papaziogas et al [31] found no difference between inguinal hernia repair with and without mesh in terms of postoperative complications and wound infection. Surgical repair using mesh is the current trend in the treatment of primary or recurrent umbilical hernias in both obese and non-obese adults due to its lower recurrence rate as compared to surgical repair by suturing (1% vs. 11%).…”
Section: Discussionmentioning
confidence: 96%
“…Bessa et al [30] stated that there was no difference between elective or emergency mesh use in terms of postoperative complications and that mesh could be used safely. Papaziogas et al [31] found no difference between inguinal hernia repair with and without mesh in terms of postoperative complications and wound infection. Surgical repair using mesh is the current trend in the treatment of primary or recurrent umbilical hernias in both obese and non-obese adults due to its lower recurrence rate as compared to surgical repair by suturing (1% vs. 11%).…”
Section: Discussionmentioning
confidence: 96%
“…However, recurrence rates did not diVer in the cited study [2]. In another study, diVerences were found in the recurrence rates but not in the infection rates.…”
mentioning
confidence: 73%
“…Several studies could show that an incarcerated groin hernia is not an absolute contraindication for the implantation of non-absorbable meshes, as the complications rates (and especially the infection rates) were similar to those after repair without the use of prosthetic material [2,3].…”
mentioning
confidence: 99%
“…[10][11][12] Prosthetic materials are not used routinely in these patients. Derici et al 13 reported that in incarcerated inguinal hernia repair, the risk of recurrence is lower with the usage of prosthetic materials.…”
Section: Discussionmentioning
confidence: 99%